Anti-Leptospira spp. antibodies in meat dealers in Tunja, Boyacá, Colombia - Gladys Elena Ataya; Adriana Maria Pedraza-Bernal; Diana Carolina Vargas; Lesly Yomara Romero; Claudia Patricia Jaimes-Bernal; Nuri Andrea Merchán-Castellanos (Sociedade Brasileira de Patologia Clínica, 2019)
ABSTRACT Leptospirosis is a zoonotic disease distributed worldwide, which is emerging as a public health problem in tropical and subtropical countries. Traditionally, it has been considered as an occupational disease. The objective of this study was to determine the serological prevalence of anti-Leptospira antibodies in meat dealers in the city of Tunja, Boyacá, Colombia. An observational, cross-sectional and descriptive study was carried out in a population of 186 operators from meat establishments in the city of Tunja. The samples were analyzed using the microagglutination test in order to determine the serovar that causes the infection. Each participant answer a survey with important questions about socio-demographic, epidemiological and occupational factors. A seroprevalence of 43% [n = 80; 95% confidence interval (CI): 36%-50%] was found. According to the serovar analysis, the distribution was: L. bratislava 30% (n = 24; 95%IC: 20%-40%), L. hardjo 21.25% (n = 17; 95%IC: 12%-30%), L. pomona 20% (n = 16; 95%IC: 11%-29%), L. icterohaemorragiae 17.5% (n = 14; 95%IC: 9%-26%), L. grippotyphosa 16.25% (n = 13; 95%IC: 8%-24%), L. canicola 16.25% (n = 13; 95%IC: 8%-24%), and L. tarassovi 11.25% (n = 9; 95%IC: 4%-18%). The prevalence rate found in this study confirms the circulation of the microorganism in these operators, which may suggest the need to reinforce hygienic-sanitary, biosecurity and prevention measures as well as the control of the disease in this population.